2012
DOI: 10.4033/iee.2012.5.11.c
|View full text |Cite
|
Sign up to set email alerts
|

Resilience: Easy to use but hard to define

Abstract: First conceptualized in the 1970s, resilience has become a popular term in the ecological literature, used in the title, abstract, or keywords of approximately 1% of papers identified by ISI Web of Science in the field of environmental sciences and ecology in 2011. However, many papers make only passing reference to the term and do not explain what resilience means in the context of their study system, despite there being a number of possible definitions. In an attempt to determine how resilience is being used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 22 publications
0
38
0
Order By: Relevance
“…Resilience was introduced to the ecological literature with a clear and specific definition (Holling, 1973), but nowadays resilience is most often used in a vague and undefined manner, as a hook to attract an audience rather than being a truly meaningful concept driving research or conservation outcomes (Brand and Jax, 2007;Myers-Smith et al, 2012). Despite conceptual vagueness, its intuitive appeal is evident in its wide-spread adoption in policy and management documents (e.g., Benson and Garmestani, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Resilience was introduced to the ecological literature with a clear and specific definition (Holling, 1973), but nowadays resilience is most often used in a vague and undefined manner, as a hook to attract an audience rather than being a truly meaningful concept driving research or conservation outcomes (Brand and Jax, 2007;Myers-Smith et al, 2012). Despite conceptual vagueness, its intuitive appeal is evident in its wide-spread adoption in policy and management documents (e.g., Benson and Garmestani, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These three components jointly comprise a 'response model' (Fig. 4), that is, an explicit statement of the anticipated relationships between proxies, disturbances and resilience properties , Myers-Smith et al 2012, Hodgson et al 2015. A response model should provide the necessary conceptual (heuristic) and measurable (quantitative) framework for assessing long-term ecosystem resilience.…”
Section: Defining Resiliencementioning
confidence: 99%
“…In a large review of the ecological literature, Myers-Smith et al ( 2012 ) found that resilience was used in many ambiguous and contradictory ways. Some authors, like Holling ( 1973 ) view stability and resilience as distinct properties; others, like Harrison ( 1979 ) defi ne resilience as a single aspect of stability.…”
Section: Concepts and Synthesismentioning
confidence: 99%